Diurnal and Seasonal Patterns of Methane Emissions from a Dairy Operation in North China Plain - Zhiling Gao; Huijun Yuan; Wenqi Ma; Jianguo Li; Xuejun Liu; Raymond L. Desjardins (Advances in Meteorology)
In China, dairy cattle managed in collective feedlots contribute about 30% of the milk production and are believed to be an important contributor to national methane emissions. Methane emissions from a collective dairy feedlot in North China Plain (NCP) were measured during the winter, spring, summer, and fall seasons with open-path lasers in combination with an inverse dispersion technique. Methane emissions from the selected dairy feedlot were characterized by an apparent diurnal pattern with three peaks corresponding to the schedule of feeding activities. On a per capita basis, daily methane emission rates of these four seasons were 0.28, 0.32, 0.33, and 0.30 kg head−1 d−1, respectively. In summary, annual methane emission rate was 112.4 kg head−1 yr−1 associated with methane emission intensity of 32.65 L CH4 L−1 of milk and potential methane conversion factor Ym of 6.66% of gross energy intake for mature dairy cows in North China Plain.